2014
DOI: 10.5455/ijlr.20140423043726
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Breeding Practices and Selection Criteria of Sheep Breed in Selale Area, Central Ethiopia

Abstract: This study was aimed to generate organized information on traditional breeding practices and selection criteria for indigenous sheep types in two districts of Selale area. A total of 300 households (150 in Debre Libanos and 150 in Wuchale district) were randomly sampled for the interview in selected and surrounding Kebeles. A semi-structured questionnaire and group discussion were used to gather sheep breeding practices and selection criteria in the area. The result showed that most of the households heads are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
5
5
1
Order By: Relevance
“…The pattern that allows mating within relatives can be associated with accumulation of inbreeding over time. Those in agreement with that of Getachew et al (2010); Abera et al (2014a) reported that the mating system of small ruminant under smallholder farmers are predominantly uncontrolled. Similarly, studies in the country reported that natural mating was a method to breed different livestock species and almost all farmers practiced this system (Menbere, 2005).…”
Section: Breeding Ram Ownership and Mating Systemsupporting
confidence: 91%
See 3 more Smart Citations
“…The pattern that allows mating within relatives can be associated with accumulation of inbreeding over time. Those in agreement with that of Getachew et al (2010); Abera et al (2014a) reported that the mating system of small ruminant under smallholder farmers are predominantly uncontrolled. Similarly, studies in the country reported that natural mating was a method to breed different livestock species and almost all farmers practiced this system (Menbere, 2005).…”
Section: Breeding Ram Ownership and Mating Systemsupporting
confidence: 91%
“…Similarly, this result was in lined with Getachew (2008) report appearance or conformation ranked first for both Afar and Menz sheep owners with an index of 0.35 and 0.29, respectively and this result was similar with in selecting a breeding ram, appearance /conformation ranked first for both DebreLibanos and Wuchale sheep owners with an index of 0.42 and 0.311, respectively (Abera et al, 2014a). And also this result was comparable with appearance or body size was ranked first by sheep owners in Basonawerena and Angolelatera with an index of 0.32, and 0.26, respectively (Haile et al, 2015).…”
Section: Breeding Rams Selection Criteriasupporting
confidence: 82%
See 2 more Smart Citations
“…This highest correlation of wither height and chest girth with body weight than other body measurements is in line with other results (Gizaw et al 2008;Getachew et al 2009;Alemayehu 2011;Abera et al 2016). The strong correlation of different measurements with body weight would imply these measurements can be used as indirect selection criteria to improve live weight (Gizaw et al 2008;Getachew et al 2009;Abera et al 2014;Mohammed et al 2015;Abera et al 2016;Bireda et al 2016) or could be used to predict body weight. The high correlation coefficients between body weight and body measurements for male and female suggest that either of these variables or their combination could provide a good estimate for predicting the live weight of sheep from body measurements.…”
Section: Correlation Between Body Weight and Linear Body Measurementsmentioning
confidence: 99%